Pepsin and carbonic anhydrase isoenzyme III as diagnostic markers for laryngopharyngeal reflux disease - Johnston, Nikki; Knight, John; Dettmar, Peter W; Lively, Mark O; Koufman, Jamie (The Laryngoscope, 2004)
The objective was to investigate the potential use of pepsin and carbonic anhydrase isoenzyme III (CA-III) as diagnostic markers for laryngopharyngeal reflux disease. Prospective cell biological investigation was conducted of laryngeal biopsy specimens taken from 9 patients with laryngopharyngeal reflux disease and 12 normal control subjects using antibodies specific for human pepsin (produced in the authors' laboratory within the Department of Otolaryngology at Wake Forest University Health Sciences, Winston-Salem, NC) and CA-III. Laryngeal biopsy specimens were frozen in liquid nitrogen for Western blot analysis and fixed in formalin for pepsin immunohistochemical study. Specimens between two groups (patients with laryngopharyngeal reflux disease and control subjects) were compared for the presence of pepsin. Further analyses investigated the correlation between pepsin, CA-III depletion, and pH testing data. Analysis revealed that the level of pepsin was significantly different between the two groups (P < .001). Secondary analyses demonstrated that presence of pepsin correlated with CA-III depletion in the laryngeal vocal fold and ventricle (P < .001) and with pH testing data in individuals with laryngopharyngeal reflux disease. Pepsin was detected in 8 of 9 patients with laryngopharyngeal reflux disease, but not in normal control subjects (0 of 12). The presence of pepsin was associated with CA-III depletion in the laryngeal vocal fold and ventricle. Given the correlation between laryngopharyngeal reflux disease and CA-III depletion, it is highly plausible that CA-III depletion, as a result of pepsin exposure during laryngopharyngeal reflux, predisposes laryngeal mucosa to reflux-related inflammatory damage.